The universalizability of the categorial imperative: Re-examining Kants Maxim of Duty - Pathak, Krishna Mani (2010)
In this dissertation, I defend Kantian ethics in terms of the universalizability of moral duties as moral laws against relativistic ethics like traditionalism and communitarianism. The problem I deal with, in special reference to Kant, is whether our actions are or should be judged by local moral determinants like individuality, community, religion or society, or by universal determinants of Kantian spirit. Those who follow local moral determinants, criticize Kantian universalizability. But I consider universality to be a strong moral determinant and therefore I defend it, and Kant. My argument, which I develop comprehensively in this dissertation, is twofold: Firstly, local determinants are based on historicism and therefore limited in scope; they leave room for partiality and discrimination among individuals. They are also dually-standardized – one for the first person (I use the term agent) and another for the second and third agents, all of whom differ from each other. Secondly, local determinants considered to be moral criteria are challenging to justify: Their projection of what a person is is not the only or real picture of a person as a moral agent. In other words, local determinants don't affect––or their proponents like MacIntyre and Taylor overlook––our deep sense of moral orientation, which deems every human being as the same. Our deep sense of morality has a need for a common standard of morality. With these arguments, I claim that the Kantian model of morality, in contrast, presents a real picture of a person and his sense of morality, though it is quite hard to find a person in the real world who acts in accordance with this moral sense. But our failure in following our deep moral sense does not mean that morality is a matter of individual choice or is merely locally-determined. The universal moral law is, after all, supreme and something to be achieved in the realization of what we are as moral and autonomous beings. The concept of local moral determinants is in fact weak in the sense that one can justify a wrong and irresponsible action as a right action, whereas, universal determinants prohibit us from following such a justification of a wrong action as right. In brief, this dissertation aims to critically evaluate the two kinds of determinants and their link to our practical life from a moral point of view. Another crucial dimension does remain in the debate at hand––the epistemic dimension––but due to the specificity of the project shall remain untouched in this dissertation.